What is the relationship between type 2 diabetes mellitus status and the neuroradiological correlates of cerebral small vessel disease in adults? Protocol for a systematic review. Issue 1 (December 2017) - Funnell, Clark; Doyle-Waters, Mary; Yip, Samuel; Field, Thalia
Abstract Background Cerebral small vessel disease (CSVD) is a common cause of stroke, dementia, and functional decline. In recent years, neuroradiologic correlates of CSVD have been identified. These imaging findings, best characterized on magnetic resonance imaging (MRI), include some combination of white matter hyperintensities, lacunes, cerebral microbleeds, enlarged perivascular spaces, and cerebral atrophy. Though some cohorts have reported that participants with type 2 diabetes mellitus (T2DM), an important risk factor for CSVD, may have a distinct neuroradiologic phenotype, this relationship is not well-characterized. Adults with diabetes mellitus have a two- to threefold higher incidence of ischemic stroke compared to controls and are an increasingly important population given global trends of increasing diabetes prevalence. This study aims to determine if adults with CSVD and T2DM have a distinct neuroradiologic phenotype. Methods A systematic search of the literature will be conducted to find articles that report the MRI features of CSVD in a cohort of participants including those with and without type 2 diabetes mellitus (T2DM). A number of databases will be searched including MEDLINE, Embase, CINAHL, and Web of Science. Proceedings and abstracts from key conferences will also be reviewed and relevant journals hand searched for additional papers. The references from selected papers will be scanned. Screening of potential articles, data extraction, and quality appraisal will be performed in duplicate by independent reviewers. Odds ratios and 95% confidence intervals for the presence versus absence of each neuroradiologic correlate of interest from each included study will be calculated. If sufficient homogeneity exists among studies, a meta-analysis will be performed for each neuroradiologic correlate of CSVD. If heterogeneity of studies precludes data pooling, results will be presented in narrative form. Discussion Determining whether a distinct neuroradiologic phenotype of CSVD exists in adults with T2DM will provide insight into the underlying mechanisms of CSVD and guide future research on therapeutic targets. Systematic review registration PROSPEROCRD42016046669